Efektivitas Pembelajaran Digital Terintegrasi di Era Pendidikan 4.0 pada Modul Ajar Guru Bahasa Indonesia di SMA - Juliana, Juliana; Astuti, Nia; Yuhafliza, Yuhafliza (Universitas Negeri Padang, 2026)
This study aims to describe the effectiveness of integrated digital learning in the Indonesian language teaching modules for senior high school and to evaluate teachers’ and students’ perceptions in the era of Education 4.0. The research employed a descriptive qualitative approach with observation, questionnaires, and documentation as data collection techniques. The subjects consisted of 3 teachers and 39 students of grades X, XI, and XII at SMAIT Entrepreneur Muhammadiyah Bireuen. The instruments were based on five components of learning modules: self-instruction, self-contained, stand-alone, adaptive, and user-friendly. The findings revealed that integrated digital learning was effectively implemented. Teachers successfully integrated digital media such as PowerPoint, learning videos, Quizizz, Kahoot, and Canva, making the learning process more interactive and independent. Students actively participated and managed to follow all activities without relying on textbooks. More than 90% of students agreed that digital learning increased their enthusiasm and motivation to learn. In conclusion, integrated digital learning is highly effective in improving the quality of Indonesian language learning and is feasible to be applied as an innovative strategy in the digital transformation era.Keywords: integrated digital learning in the era of Education 4.0, Indonesian language teaching module.